A Retrospective Observational Cohort Analysis of Oncology Patients with Febrile Neutropenia in the Emergency Department of a Tertiary Care Hospital in Oman - Badar Al-Aamri; Aisha AL Breiki; Darpanarayan Hazra; Talib Al-Aamri; Manar Al-Shehi (Current Medical Issues)
Background: Febrile neutropenia, a critical concern in chemotherapy-treated oncology patients, demands swift and guideline-based management. This study evaluated guideline adherence and clinical outcomes in the management of febrile neutropenia in oncology patients in the emergency department (ED). Methods: This retrospective study was conducted over 4 years. The primary focus was the evaluation of adherence to guidelines for patient disposition and clinical outcomes. Data were retrieved from the hospital’s electronic records, systematically organized, and analyzed. Results: A total of 121 febrile neutropenic cases were included in the study. Of these, 52.9% were classified as low risk, with 44.6% having hematological malignancies and 55.4% having solid malignancies. Most patients (89.3%) presented with active cancer, and the mean neutrophil count was 0.18. High-risk patients exhibited significantly higher rates of positive blood cultures (31.6% vs. 1.6%) and positive urine cultures (20.8% vs. 7.7%). Chest X-rays were positive in 5.5% of low-risk patients and 23.2% of high-risk patients. Fungal infection rates were 1.6% in low-risk patients and 29.8% in high-risk patients. Complications were more frequent in high-risk patients, including sepsis-induced hypotension in 6.3% of low-risk patients and 43.9% of high-risk patients. Deaths occurred in 21.1% of high-risk patients, and intensive care unit (ICU) admissions were 24.6% in the high-risk group, with no ICU admissions in the low-risk group. Binary logistic regression revealed that male patients had a 60% lower risk of guideline discordance than female patients (odds ratio [OR]: 0.400, 95% confidence interval [CI]: 0.180-0.891, P = 0.025), whereas diabetic patients had a 75% lower risk than nondiabetic patients (OR: 0.254, 95% CI: 0.069–0.934, P = 0.039). Conclusion: As expected, high-risk patients demonstrated greater illness severity than low-risk patients, with higher rates of admission, sepsis-induced hypotension, and mortality.